Bibliometric analysis of subject trends and knowledge structures of gut microbiota - Yue, Yuan-Yi (World J Clin Cases, 2020)
BACKGROUND: Gut microbiota is an emerging field of research, with related research having breakthrough development in the past 15 years. Bibliometric analysis can be applied to analyze the evolutionary trends and emerging hotspots in this field. AIM: To study the subject trends and knowledge structures of gut microbiota related research fields from 2004 to 2018. METHODS: The literature data on gut microbiota were identified and downloaded from the PubMed database. Through biclustering analysis, strategic diagrams, and social network analysis diagrams, the main trend and knowledge structure of research fields concerning gut microbiota were analyzed to obtain and compare the research hotspots in each period. RESULTS: According to the strategic coordinates and social relationship network map, Clostridium Infections/microbiology, Clostridium Infections/therapy, RNA, Ribosomal, 16S/genetics, Microbiota/genetics, Microbiota/immunology, Dysbiosis/immunology, Infla-mmation/immunology, Fecal Microbiota Transplantation/methods, Fecal Microbiota Transplantation can be used as an emerging research hotspot in the past 5 years (2014-2018). CONCLUSION: Some subjects were not yet fully studied according to the strategic coordinates; and the emerging hotspots in the social network map can be considered as directions of future research.